2008
DOI: 10.2131/jts.33.37
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling of methapyrilene-induced hepatotoxicity in rat

Abstract: -The present study was conducted as a model case of the toxicogenomics approach for analyzing toxicological mechanisms and toxicity assessments in the early stage of drug development by comparing with classical toxicology data. Methapyrilene (MP) 100 mg/kg produced obvious histopathological changes in liver of rats by single or repeated dose up to 28 days with significant elevation of ALT and AST. In the middle dose groups (30 mg/kg MP), no apparent changes were noted in blood biochemical data by single dosing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The ultimate purpose of toxicogenomics is developing a toxicity prediction system using suitable classifier probes through microarray techniques as a replacement of traditional toxicity tests 2,10, [16][17][18][21][22][23][24][25][26][27] . Also, it is important to accumulate data on classifier probes of sufficient numbers of drugs in order to predict, but there are studies using only a few drugs 8,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate purpose of toxicogenomics is developing a toxicity prediction system using suitable classifier probes through microarray techniques as a replacement of traditional toxicity tests 2,10, [16][17][18][21][22][23][24][25][26][27] . Also, it is important to accumulate data on classifier probes of sufficient numbers of drugs in order to predict, but there are studies using only a few drugs 8,28,29 .…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of TGP2 was to identify biomarkers for diagnosing and/or predicting compound toxicity based upon the gene expression data accumulated in TGP1. A number of biomarkers and gene expression profiles indicative of exposure to particular toxic compounds were reported following the TGP1 and TGP2 studies (Kiyosawa et al, 2006;Morishita et al, 2006;Tamura et al, 2006aTamura et al, , 2006bKiyosawa et al, 2007;Omura et al, 2007;Hirode et al, 2008Hirode et al, , 2009aHirode et al, and 2009bUehara et al, 2008aUehara et al, , 2008bUehara et al, and 2008cKondo et al, 2009;Minowa et al, 2012). Prior to use of the gene expression data accumulated during TGP1 in future drug discovery studies, the procedures used to analyze gene expression must be validated and the degree of inter-laboratory variation must be assessed.…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of microarray expression profiling techniques, several attempts have been made to address induction of liver toxicity in short-term rodent experiments during the preclinical phase of drug development [7][8][9][10]. These studies have shown that hepatotoxicants induce a distinct pattern of deregulated genes at an early stage that may allow detection of arising hepatic toxicity.…”
Section: Introductionmentioning
confidence: 99%